The effect of technology-exploration on product innovation: an analysis based on Korean manufacturing SMEs - Hojin Lee; Sangyoon Cha; Heejun Park (International Journal of Quality Innovation, 2016)
Today, fierce competition drives firms in their continual efforts to introduce products with a higher degree of novelty into the market. There is a growing need to understand important activities so as to achieve product innovation. This empirical study demonstrates the effect of technology-exploration, including outsourcing R&D, external networking, customer involvement, and inward IP licensing, on product innovation, especially considering the degree of the novelty of the manufactured products. Using data from a sample of small and medium Korean manufacturing firms, our results show that technology-exploration are crucial determining factors as to whether low or higher degree of novelty is achieved in product innovation. The positive impact of higher degree of innovation novelty comes from customer involvement and outsourcing R&D. In addition, customer involvement has positive impact only on low degree of innovation. Other practices have no impact on either low or high degree of novelty in product innovation
Keywords: 650; Open innovation; Technology-exploration; Product Innovation; SMEs